2009
DOI: 10.1016/j.bbadis.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced metabolic disturbances as modulators of brain homeostasis

Abstract: A number of metabolic disturbances occur in response to the consumption of a high fat Western diet. Such metabolic disturbances can include the progressive development of hyperglycemia, hyperinsulemia, obesity, metabolic syndrome, and diabetes. Cumulatively, diet-induced disturbance in metabolism are known to promote increased morbidity and negatively impact life expectancy through a variety of mechanisms. While the impact of metabolic disturbances on the hepatic, endocrine, and cardiovascular systems are well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…Indeed, the adverse effects of metabolic syndrome on brain physiology in rodents have been very well established by our labs (Pistell et al 2010, Bruce-Keller et al 2009), (Bruce-Keller et al 2010), (White et al 2009), (Zhang et al 2009), (Studzinski et al 2009) and by others (Farr et al 2008), (Winocur & Greenwood 2005), (Stranahan et al 2008), (Jurdak et al 2008), (Molteni et al 2002), and increased gliosis is a very common finding in rodent studies of diet-induced metabolic dysfunction. Reactive gliosis is strongly associated with brain inflammation, and increased inflammation is a key physiologic feature of obesity (reviewed in (Hotamisligil 2006).…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, the adverse effects of metabolic syndrome on brain physiology in rodents have been very well established by our labs (Pistell et al 2010, Bruce-Keller et al 2009), (Bruce-Keller et al 2010), (White et al 2009), (Zhang et al 2009), (Studzinski et al 2009) and by others (Farr et al 2008), (Winocur & Greenwood 2005), (Stranahan et al 2008), (Jurdak et al 2008), (Molteni et al 2002), and increased gliosis is a very common finding in rodent studies of diet-induced metabolic dysfunction. Reactive gliosis is strongly associated with brain inflammation, and increased inflammation is a key physiologic feature of obesity (reviewed in (Hotamisligil 2006).…”
Section: Discussionmentioning
confidence: 77%
“…Studies from our laboratory and others' have demonstrated that HFDs exacerbate tissue dysfunction in aging animals (11,29,46,68,76). Additionally, studies from our laboratory and others' have shown that HFDs promote much greater amounts of adipose gain, and presumably adipose tissue dysfunction, compared with younger animals (46,50,66).…”
Section: Discussionmentioning
confidence: 85%
“…Because of the potential for age-related changes in adipose function to modulate overall health and promote metabolic disease, there is a growing interest in studying aging adipose tissue. White adipose tissue is recognized as an important modulator of multiple physiological processes and is strongly linked to the development of multiple morbidities (8,16,46,66,76). The ability of adipose tissue to exert these effects comes from alterations in the endocrine functions of adipose (22,52,71) as well as the contributions of adipose tissue to glucose and lipid homeostasis (10,26,37,75).…”
mentioning
confidence: 99%
“…Rodents exposed to a fructose diet display physiological signs of MetS such as increased hepatic lipid and triglyceride level (Agrawal and Gomez-Pinilla, 2012; Kelley et al, 2004), and peripheral insulin resistance (Agrawal and Gomez-Pinilla, 2012; Dekker et al, 2010). Consumption of fructose has recently been recognized as a critical instigator of the current epidemic of metabolic disorders in humans (Dhingra et al, 2007; Ishimoto et al, 2013; Lanaspa et al, 2013; Lyssiotis and Cantley, 2013; Stanhope et al, 2009), and its effects on compromising neuronal function are becoming alarming (Farooqui et al, 2011; Newcomer, 2007; Raji et al, 2010; Zhang et al, 2009). We have adopted fructose in the drinking water as a rodent model to promote metabolic disturbances such as peripheral and central insulin resistance, lipid dysregulation, and disrupted insulin signaling (Figs.…”
Section: The Threat Of the New Epidemic Of Metabolic Disordersmentioning
confidence: 99%